Role of Somatostatin Receptor in Pancreatic Neuroendocrine Tumor Development, Diagnosis, and Therapy - Hu, Yuheng; Ye, Zeng; Wang, Fei; Qin, Yi; Xu, Xiaowu; Yu, Xianjun; Ji, Shunrong (Frontiers in Endocrinology, 2021)
Pancreatic neuroendocrine tumors (pNETs) are rare and part of the diverse family of neuroendocrine neoplasms (NENs). Somatostatin receptors (SSTRs), which are widely expressed in NENs, are G-protein coupled receptors that can be activated by somatostatins or its synthetic analogs. Therefore, SSTRs have been widely researched as a diagnostic marker and therapeutic target in pNETs. A large number of studies have demonstrated the clinical significance of SSTRs in pNETs. In this review, relevant literature has been appraised to summarize the most recent empirical evidence addressing the clinical significance of SSTRs in pNETs. Overall, these studies have shown that SSTRs have great value in the diagnosis, treatment, and prognostic prediction of pNETs; however, further research is still necessary.